Образование возбужденных молекул водорода при рекомбинации атомов водорода в дальнодействующих электрических полях частиц, расположенных на электронейтральной поверхности реактора - Г. Н. Саргсян (ՀՀ ԳԱԱ հրատ.)
Проведено исследование роли частиц с большим значением дипольного момента и ионов, адсорбированных на электронейтральной поверхности реактора, как источников формирования высококолебательно-возбужденных молекул при рекомбинации атомов в дальнодействующих электрических полях этих (адсорбированных) частиц. Կատարված է էլեկտրոնեյտրալ մակերևույթի վրա տեղակայված մեծ դիպոլային մոմենտ ունեցող մասնիկների և իոնների դերի հետազոտումը որպես բարձր տատանողական գրգռված ջրածնի մոլեկուլների առաջացման աղբյուրներ: The role of particles with the great dipole moment and ions situated on an electro neutral surface, as source of high vibrational excited molecules of hydrogen, a corollary of a recombination of atoms of hydrogen in their long-range electric fields is considered. At chemical reactions with the chain mechanism, frequently products or the active intermediate particles are adsorbed on a surface of a reaction vessel. Great magnitudes of the dipole moment have the majority of these products or owing to the composite rearrangements with other particles can, will undergo a surface ionization. Such particles create around of themselves a long-range electric field and can be centers of condensation atoms and radicals. These particles gradually lose the kinetic energy and, eventually, they are stabilized at the bottom of an energy barrier.
Keywords: Physical Chemistry